1991
DOI: 10.1099/00221287-137-3-601
|View full text |Cite
|
Sign up to set email alerts
|

Reference collection of strains of the Salmonella typhimurium complex from natural populations

Abstract: A collection of 72 reference strains of the Sufmoneffu typhimurium complex of clones recovered from a variety of hosts and environmental sources in diverse geographic locations has been established for use in studies of variation in natural populations. Included are strains of the serovars S typhimurium, S. sdntpuuf, S. heidefberg, S.purutyphi B (including varietyjatra) and S. muenchen. The strains, which have been characterized by enzyme electrophoresis for allelic variation in 24 chromosomal structural genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
90
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(94 citation statements)
references
References 5 publications
3
90
0
Order By: Relevance
“…Comparison of the serotype Typhimurium LT2 genome with that of the pigeon isolate phage types DT2 and DT99 by microarray analysis supports several lines of previously published work. First, the results of the microarray analysis showed that the genetic differences between these isolates are small, and they confirmed previous results that different isolates of the same serotype are very closely related (3,4). A recent pulsed-field gel electrophoretic analysis of 38 DT99 pigeon isolates and 18 isolates from other species indicated that the DT99 isolates examined were essentially clonal (24).…”
Section: Vol 186 2004 Differences Between Serotype Typhimurium Isolsupporting
confidence: 69%
See 1 more Smart Citation
“…Comparison of the serotype Typhimurium LT2 genome with that of the pigeon isolate phage types DT2 and DT99 by microarray analysis supports several lines of previously published work. First, the results of the microarray analysis showed that the genetic differences between these isolates are small, and they confirmed previous results that different isolates of the same serotype are very closely related (3,4). A recent pulsed-field gel electrophoretic analysis of 38 DT99 pigeon isolates and 18 isolates from other species indicated that the DT99 isolates examined were essentially clonal (24).…”
Section: Vol 186 2004 Differences Between Serotype Typhimurium Isolsupporting
confidence: 69%
“…Serotype Typhimurium consists of a collection of isolates that are more closely related to each other than they are to other S. enterica serotypes (3,4) and are distinguishable from each other by phage typing and other epidemiologic typing methods (27). Epidemiologic evidence indicates that certain phage types of serotype Typhimurium have a narrow host range and are very frequently isolated from particular host species and rarely from other mammals or birds.…”
mentioning
confidence: 99%
“…The name "virulence antigen" notwithstanding, a casual relationship of this polysaccharide to virulence has not been convincingly demonstrated, even for S. typhi, in which it has been extensively studied (12,33). When tested in the mouse model, several Vi-positive strains of S. dublin have been found to be no more virulent than Vi-negative strains (6,29 typhimurium (4,5). Table 4.…”
Section: Methodsmentioning
confidence: 99%
“…Inversions with endpoints in the seven copies of the rrn operons are common in S. typhimurium (15) and E. coli (17); the frequency of inversions at other sites varies from low to undetectable (18). This high frequency of rearrangements in culture, combined with the stability of the chromosome through evolution, indicates that cells with rearrangements are strongly selected of which has a cleavage site for the endonuclease I-CeuI (6,7). The seven I-Ceul fragments are in the order ABCDEFG.…”
mentioning
confidence: 99%